VIRTUALIZATION OF IDENTITY IN THE CONTEXT OF SELF-REALIZATION OF A PERSONALITY - Y. V. Lyubiviy; R. V. Samchuk (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The research is aimed at clarifying the essence of virtual reality and its productive role in the self-realization of the individual, as well as the importance in the process of self-realization of the individual to expand the dimensions of his identity by including virtual dimensions. To do this, the process of formation of the phenomenon of virtual identity in the environment of virtual reality is revealed and the influence of productive human activity in virtual reality on the nature of virtualization of its identity is turned out. Theoretical basis of the work is understanding virtual reality as a combination of conscious productive imagination as its attribute, on the one hand, and the technological component in the form of a computer and related programs on the other hand. An anthropological prerequisite for virtual reality is the ability of the man’s creative imagination to calculate and choose the best model from many mental design ones, using, among other things, horizontal computer networks, which form a virtual identity. Originality. It was found that a necessary condition for the formation of a virtual identity is the exchange of results of productive and intermediary activities between Internet users, which they carry out in Internet networks with the help of virtual reality itself. Accordingly, philosophical studies of virtual reality (R. Burrows, G. Cooper, M. Heim, R. Harper, N. Green, J. Juul, B. Loader, N. McDonnell, N. Wildman, S. Muncer, G. M. Murtagh, S. Nettleton, O. Ollinaho, N. Pleace, G. M. P. Swann, T. P. Watts) are gradually supplemented by research in the field of virtual identity (R. Baltezarevic, B. Baltezarevic, V. Baltezarevic, D. Deh, D. Glodovic, Este N. Beck, P. Kwiatek, R. A. Hardesty, B. Sheredos, N. McDonnell, N. Wildman, O. Ollinaho, E. J. Ramirez, S. LaBarge, J. Spiegel). Competitive production and distribution of human livelihoods through creative project work in virtual reality in interaction and communication with Others in a rapidly changing society requires the expansion of identity, including virtual dimensions. In the modern world self-realization of the individual includes the expansion of identity through its virtualization. Conclusions. A person’s productive activity in computer virtual reality – as an auxiliary tool of his creative imagination –creates his virtualized identity in solidarity and competitive interaction with Others, promotes self-realization of his personality and makes his holistic identity more flexible. Accordingly, philosophical studies of virtual reality over time are supplemented by philosophical anthropology studies of virtual identity.